Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw dalam Meningkatkan Motivasi dan Hasil Belajar Siswa di MAT Daarut Tahfizh Al-Ikhlas - Ulfa, Nabilla; Kamal, Samsul; Hanim, Nafisah; Taib, Eva Nauli; Eriawati, Eriawati (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2025)
This study aims to determine the motivation and learning outcomes of students with the application of the Jigsaw type cooperative learning model on human respiratory system material at MAT Daarut Tahfizh Al-Ikhlas. This study used a true experimental design with a pretest-posttest control group type of research. Class XI-3 as the experimental class used the Jigsaw model, while class XI-2 as the control class used conventional learning. Data collection techniques were carried out through motivation questionnaires and learning outcomes tests, then analyzed by independent sample t-test. The results showed a significant increase in student motivation and learning outcomes in the experimental class. The average N-Gain value of the experimental class was 0.72 (high category), while the control class was 0.43 (medium category). The students' learning motivation score in the experimental class also reached the “very high” category. Thus, the Jigsaw type cooperative learning model proved effective in improving students' motivation and learning outcomes.